2012
DOI: 10.1186/1556-276x-7-344
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-deposited fluoropolymer film mask for local porous silicon formation

Abstract: The study of an innovative fluoropolymer masking layer for silicon anodization is proposed. Due to its high chemical resistance to hydrofluoric acid even under anodic bias, this thin film deposited by plasma has allowed the formation of deep porous silicon regions patterned on the silicon wafer. Unlike most of other masks, fluoropolymer removal after electrochemical etching is rapid and does not alter the porous layer. Local porous regions were thus fabricated both in p+-type and low-doped n-type silicon subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…This type of masking layer can be employed for microelectronic applications such as MEMS, Si/PolySi hybrid substrates etc. Due to its chemical resistance, FP may be employed as a protective layer for the underlying ones in the backend electrochemical etching process [24].…”
Section: Surface Passivation By Pfp Coatingsmentioning
confidence: 99%
“…This type of masking layer can be employed for microelectronic applications such as MEMS, Si/PolySi hybrid substrates etc. Due to its chemical resistance, FP may be employed as a protective layer for the underlying ones in the backend electrochemical etching process [24].…”
Section: Surface Passivation By Pfp Coatingsmentioning
confidence: 99%
“…This capacitive effect is more pronounced in the case of thin layers with high dielectric constant (for example, Si 3 N 4 ). 54 More recently, Defforge et al 55 proposed an innovative plasma deposited fluoro-polymer film for local porous silicon formation. This mask is inert in HF acid and can be removed easily using oxygen plasma.…”
Section: Porous Silicon Localizationmentioning
confidence: 99%
“…In the literature, different kinds of HF resistant materials have been tested and proposed as a masking layer for deep PS formation. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Among them, silicon nitride (Si x N y ), 15,16 bilayer of polycrystalline silicon/silicon dioxide, 18,22 or tri-layer stack of poly-Si/Si x N y /SiO 2 12 are the most widely used masking materials due to the maturities of deposition techniques and the compatibility with current silicon processing. However, the common drawback of all these masking materials is the complicated post-etching mask removal procedures when bare silicon surface is ultimately required.…”
Section: Introductionmentioning
confidence: 99%
“…29 By carefully choosing gas monomer and kinetic formation parameters such as RF power input, gas pressure, etc., it is, indeed, possible to synthesize PPFP with desired characteristics. 29 The recent work by Defforge et al 27 has indicated that, by cosynthesizing trifluoromethane (CHF 3 ) and ethylene (C 2 H 4 ), PPFP with excellent HF resistance is deposited on silicon wafers. As an organic material, this film enables a rapid O 2 plasma removal with a minor damage on the PS layer (nearsurface oxidation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation